Narcissism and perceived stress among Italian hospital nurses during COVID-19: the moderator role of age. (4th January 2023) - Leonelli, Simona; Primavera, Emanuele
The COVID-19 pandemic has led to the reorganisation and creation of new hospitals, shocking healthcare workers' routines. This study investigates nurses' stress perception in COVID-19 time and how some antecedents (i.e., narcissism and age) impact it. The paper focuses on two facets of narcissism, i.e., Leadership/Authority and Entitlement/Exploitativeness. We recruited 281 nurses who completed an online survey investigating their stress perception levels and personalities. Data are analysed using hierarchical linear modelling and simple slope analyses. Results show that Leadership/Authority negatively influences stress perception, while Entitlement/Exploitativeness positively influences it. Furthermore, nurses' age moderates the above relationships. The study contributes to narcissism, stress and nursing literature, showing some positive facets of narcissism that might be useful for reducing stress perception and facilitating human relationships in the work environment, both in emergency and non-emergency contexts.